Implementasi Good Corporate Governance (GCG) dalam Pengelolaan Manajemen Risiko pada PT. BPRS Jam Gadang (Perseroda) - Ramadhani, Fadhila Rahadatul; Martilova, Novera (Lembaga Yasin AlSys, 2024)
This research is motivated by the occurrence of fluctuations in the increase in the number of customers and the increase in the number of problematic financing customers of PT. BPRS Jam Gadang Perseroda, because the number of problematic financing customers is closely related to the implementation of good corporate governance (GCG) in risk management. This study aims to determine how the Implementation of Good Corporate Governance (GCG) in Risk Management at PT. BPRS Jam Gadang (PERSERODA). The research that the author did was with a qualitative approach method, the data sources that the author took were from primary data and secondary data. And data collection techniques with observation, interviews, and documentation. While the data analysis technique obtained using data analysis, namely data reduction, data display, conclusions and verification. Based on the results of research and analysis that the authors conducted, it can be concluded that the Implementation of Good Corporate Governance (GCG) in Risk Management at PT BPRS Jam Gadang (PERSERODA) shows that the company has run it well, adhering to principles such as transparency, accountability, responsibility, openness, and independence. The bank develops risk management strategies to effectively manage its activities and maintain good operational performance. And there are two obstacles faced, namely laws and regulations made by the bank, and the quality of human resource investment.